Identifikasi epitop dari Streptococcus mutans terhadap sekretori Imunoglobulin A saliva (The identification of Streptococcus mutans epitopes to secretory Immunoglobulin A saliva) - Anita Yuliati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
S. mutans is one of the etiology agent of dental caries, these bacteria have a surface protein of about 185 kDa named Ag I/II. The secretory of sIgA saliva to Ag I/II of S.mutans has shown to be able to prevent colonization in human oral cavity. Peptides derived from the 824 to 853 residues of the P region of antigen I/II S. mutans related to the pathogenesis of dental caries. The aim of this study was to identify the overlapping sequence of amino acids (epitope) derived from the 624 to 853 residues of P of antigen I/II S. mutans to sIgA saliva on caries and caries-free subject in a observational cross sectional study. The P region of antigen I/II S.mutans was cut into 22 peptides of 9 mer sequences with an overlapping of 8 mer and an offset of 1 mer, synthesized on polyethylene pins and tested for the reactivity with an ELISA indirect method to sIgA saliva on caries and caries-free subject. The results of this study showed that amino acid sequences with TPPVKP (832–837) and TAPTKPTY (838–845) were reactive to sIgA saliva on caries and caries-free subject. The conclusion of this study was that the overlapping common sequence of amino acid (epitopes) corresponding to TPPVKP (832–837) and TAPTKPTY (838–845) was identified as caries marker epitopes in human.